Species composition of understory vegetation in coal mined land in Central Bengkulu, Indonesia - WIRYONO WIRYONO; ARIF BUHA SIAHAAN (Society for Indonesian Biodiversity, 2013)
Wiryono, Siahaan AB. 2013. Species composition of understory vegetation in coal mined land in Central Bengkulu, Indonesia. Biodiversitas 14: 31-36. Coal strip mining in forest area has destroyed forest ecosystem and created barren land. Reclamation of mined land is done by revegetating the land. In addition to planted species, pioneer species usually grow naturally in mined land. The objectives of this study were to know the species composition of understory vegetation growing naturally in coal mined land planted with Gmelina arborea in Central Bengkulu, Indonesia, and to compare that composition with that of unreclaimed coal mined land and of natural forests. Data were collected by sampling understory vegetation in study site. Each plant was identified, harvested and oven-dried to find the biomass. Results showed that the reclaimed mined land had 16 understory species from 6 families, and the abandoned mined land had 10 species from 3 families, lower than that of natural forests, which were 92 and 112. The three most important species were Scleria sumatrensis Retz, Eragrostis chariis (Schult.) Hitchc and Paspalum conjugatum Berg. The species composition of understory vegetation in reclaimed mined land had high similarity with that of abandoned mined land but was totally different from that of natural forests.